Influence Relaxation Muscle Progressive to Sleep Quality Patient with Cancer Breast - Septi Machelia Champaca Nursery; Lucia Andi Chrismilasari; Candra Kusuma Negara (Sean Institute, 2023)
Sufferer cancer breast experiences various physical problems able influence the quality of Sleep. Quality Sleep sufferer cancer breast can influence the system of immunity body, cognitive ability, and daily activity life. One intervention non pharmacology for overcoming disturbance in Sleep is the relaxation of muscle progression. Study This aims to identify the influence of relaxation muscle progress on the quality of Sleep sufferer cancer boobs. Research design using quasi-experiments. A draft study using one group pretest and post-test control group design involving 16 Respondents sufferer cancer breast. The sampling method used is non-probability sampling with a consecutive sampling technique. Quality data collection Sleep use questionnaire Pittsburg Quality Sleep Index (PSQI). Research results by the Man Whitney test obtained statistical test results p value = 0.001 (P < 0.05), indicating an influence on exercise relaxation muscle to quality Sleep sufferer cancer. With study expected that exercise relaxation muscle progress can be used as a method of easy relaxation for increased quality Sleep sufferer cancer breast so that can be applied in everyday life.